ESTER PLASTICIZERS BASED ON FATTY ACIDS FROM SOYBEAN OIL USED IN PELICULOGEN COMPOSITIONS - BORAN, Sorina; NIȚU, Sabina (Studia Universitatis Babeș-Bolyai Chemia, 2018)
In this paper, we are describing the synthesis and characterization of esters based on soybean oil fatty acids and an assessment of their potential use as plasticizers in wood, concrete or metal paints. Esters of fatty acids were obtained in a chemical reactor with microwave heating, using soybean oil fatty acids and n-butanol or isopentanol in acidic conditions.